Percutaneous implantation of self-expandable aortic valve in high risk patients with severe aortic stenosis: The first experiences in Serbia - Nedeljković, Milan A.; Beleslin, Branko; Tesić, Milorad; Vukcević, Vladan; Stanković, Goran; Stojković, Siniša; Orlić, Dejan; Bilbija, Ilija; Matković, Miloš; Simić, Tijana; Menković, Nemanja; Mrdović, Igor; et al. (Vojnosanitetski pregled, 2017)
Background/Aim. Aortic stenosis (AS) is the most common valvular heart disease in elderly people, with rather poor prognosis in symptomatic patients. Surgical valve replacement is the therapy of choice, but a significant number of patients cannot undergo surgical procedure. We presented initial experience of transcatheter aortic valve implantation (TAVI) performed in Catheterization Laboratory of the Clinic for Cardiology, Clinical Center of Serbia. Methods. The procedures were performed in 5 patients (mean age 76 ± 6 years, 2 males, 3 female) with severe and symptomatic AS with contraindication to surgery or high surgical risk. The decision to perform TAVI was made by the heart team. Pre-procedure screening included detailed clinical and echocardiographic evaluation, coronary angiography and computed tomography scan. In all the patients we implanted a self-expandable aortic valve (Core Valve, Medtronic, USA). Six months follow-up was available for all the patients. Results. All interventions were successfully performed without significant periprocedural complications. Immediate hemodynamic improvement was obtained in all the patients (peak gradient 94.2 ± 27.6 to 17.6 ± 5.2 mmHg, p < 0.001, mean pressure gradient 52.8 ± 14.5 to 8.0 ± 2.1 mmHg, p < 0.001). None of the patients developed heart block, stroke, vascular complication or significant aortic regurgitation. After 6 months, the survival was 100% with New York Heart Association (NYHA) functional improvement in all the patients. Conclusion. This successful initial experience provides a solid basis to treat larger number of patients with symptomatic AS and high surgical risk who are left untreated.